The Community Policing Evaluation Survey: Reliability, validity, and structure - McKee, Adam J. (American journal of criminal justice, 2001)
This paper describes the reliability, validity, and structure of a scale designed to evaluate community-policing programs. The Community Policing Evaluation Survey (CPES) is designed in such a way that local police agencies can implement it without the assistance of professional researchers. The scale consists of four subscales which measure (1) Quality of Contact with Police, (2) Perceptions of Crime and Disorder, (3) Personal Fear, and (4) Community Cohesion.